The Abundance and Distribution Patterns of Mussel Shell (Meretrix meretrix) in Coastal Water of Tanjung Balai Asahan North Sumatra Province - Nasution, Syafruddin; Samiaji, Joko; ', Marini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from September – Oktober 2014 in coastalwater of Tanjung Balai Asahan north Sumatra. In general the shell was a group ofinvertebrate animal (invertebrates) with its shape easy to be recognized. Mostshell were characterized by the presence of a shell that protected the body andonly a small part type was not shelled. The mussel shell M. meretrix was animportat fishery commodities as food from the sea and popular to Tanjung Balaicommunity. Tanjung Balai Asahan coastal was one of the mussel shell M.meretrix potential in north Sumatra. This research was aims to determine theabundance and distribution patterns of mussel shell M. meretrix in the intertidalzone Tanjung Balai Asahan. The method applied on this research was surveymethod. Location ofthe study were divided into 2; station 1 was away from thesettlements; while station 2 was near residential area. To get a description of theabundance distribution of mussel shell M. meretrix in the intertidal zone of thecoastal Tanjung Balai Asahan, the tidal area was divided into 4 zones by dividingthe tidal zone vertically, range from high tide to low tide.In each zone a sample taken 5 plot with plot size 1x1m2. Sediment samplewere taken by 3 points in each zone, and rolled into one, so that amount ofsediment sample by 4 sample at each station. Sample taken shell, sediment,measurement quality of the measured temperature, salinity, pH, brightness. Theresult showed that the average abundance ranged from 1.6 ind/m2to 7 ind/m2. Thepattern of distribution in the study area tend to cluster. Based on the calculation ofthe t test at each station and each zone F test on the abundance of mussel shell M.meretrix showed equally not significantly different.Keywords: Mussel shell, abundance, sediment, pattern distribution, TanjungBalai Asahan.